Identification of Student’s Spatial Perceptions of Public Elementary School Classrooms in Cirebon During The Pandemic - Satriaji, Kukuh Rizki; Santosa, Imam; Syarief, Achmad; Wibisono, Andriyanto (JPGI (Jurnal Penelitian Guru Indonesia), 2023)
During the Covid-19 pandemic, the physical presence of classrooms shifted to virtual spaces, where it changed almost all methods of delivering learning materials. Elements of space and its supports that can usually be felt in the classroom, such as furniture configuration, wall colors, information boards, teacher's desks and chairs, and others, make the class irrelevant. However, as the situation improves, there is a gradual transition from online to offline learning methods. Previous research stated that students were not satisfied with the online learning system due to a lack of engagement. This study tries to identify and review students' perceptions when they return to the classroom, starting from their conditions, tendencies, and expectations of their classrooms so that learning process can take place well. The object of this research is an elementary school, namely SDN 03 Kepongpongan, located in Cirebon Regency. The method used is participatory design approach, where the main data is obtained through the distribution of questionnaires adapted to the characteristics of the children, interviews, discussion, and the results of documentation during the activity. From the results it was found that there was a low perception between students and their classrooms. The results of this study are students' perceptions of classrooms elements that can be used for the process of re-designing classrooms after the pandemic period.